Apicomplexan F‐actin is required for efficient nuclear entry during host cell invasion. (4th October 2019) - Del Rosario, Mario; Periz, Javier; Pavlou, Georgios; Lyth, Oliver; Latorre‐Barragan, Fernanda; Das, Sujaan; Pall, Gurman S; Stortz, Johannes Felix; Lemgruber, Leandro; Whitelaw, Jamie A; Baum, Jake; Tardieux, Isabelle; et al.
Abstract: The obligate intracellular parasites Toxoplasma gondii and Plasmodium spp. invade host cells by injecting a protein complex into the membrane of the targeted cell that bridges the two cells through the assembly of a ring‐like junction. This circular junction stretches while the parasites apply a traction force to pass through, a step that typically concurs with transient constriction of the parasite body. Here we analyse F‐actin dynamics during host cell invasion. Super‐resolution microscopy and real‐time imaging highlighted an F‐actin pool at the apex of pre‐invading parasite, an F‐actin ring at the junction area during invasion but also networks of perinuclear and posteriorly localised F‐actin. Mutant parasites with dysfunctional acto‐myosin showed significant decrease of junctional and perinuclear F‐actin and are coincidently affected in nuclear passage through the junction. We propose that the F‐actin machinery eases nuclear passage by stabilising the junction and pushing the nucleus through the constriction. Our analysis suggests that the junction opposes resistance to the passage of the parasite's nucleus and provides the first evidence for a dual contribution of actin‐forces during host cell invasion by apicomplexan parasites. Synopsis: Nuclei of apicomplexan parasites represent a major obstacle that needs to be squeezed through the junctional ring bridging the host cell and the parasite during invasion. This study proposes a push‐and‐pull mechanism whereby F‐actin machinery eases nuclear passage. Super‐resolution microscopy imaging reveals that F‐actin forms a highly dynamic, cytosolic network in extracellular parasites. F‐actin independently accumulates at the posterior pole and the junctional ring during invasion. F‐actin forms a continuous network between the junction and the posterior ring that surrounds the nucleus. Mutant parasites with dysfunctional acto‐myosin exhibits decreased junctional and perinuclear F‐actin and reduced nuclear passage through the junction. Abstract : Nuclei of apicomplexan parasites represent a major obstacle that needs to be squeezed through the junctional ring bridging the host cell and the parasite during invasion. This study proposes a push‐and‐pull mechanism whereby F‐actin machinery eases nuclear passage.